Nurturing Traditional Knowledge Systems for Development - World Bank (World Bank, Washington, DC, 2012)
Traditional Knowledge systems are the essence of the social capital of the poor and the source of their survival strategies. Rooted in tradition, TK is also contemporary knowledge, defined by its inherently dynamic nature. It is constantly evolving as individual and community responses to the challenges posed by their environment.